Menilik Menilik Sikap Warga Sekolah Terhadap Siswa Berkebutuhan Khusus: Studi Di Sekolah Menengah Inklusi Jakarta - Adhissa Qonita (Journal of Research and Measurement in Psychology: JPPP, 2025)
Abstract Based on Pasal 8 Ayat A Pergub No.32 Tahun 2021 DKI Jakarta area directs that all public schools must accept students with special needs and run inclusive education. The running of inclusive schools cannot be separated from the attitude shown by school residents towards students with special needs. However, the presence of students with special needs is not immediately accepted by the school community, therefore the expected positive attitude does not necessarily arise. This study was conducted with 105 teachers and 286 students in inclusive secondary schools in Jakarta. The measurement tools used were the Chedoke-McMaster Attitudes Toward Children with Handicaps (CATCH) for students and the multidimensional attitudes toward inclusive education scale (MATIES) for teachers. The study results show that most students still show a neutral attitude towards students with special needs. Meanwhile, teachers' attitudes towards inclusive education still do not differ much between positive and negative attitudes. These results show that although it has developed, not most of the school community has shown positive attitudes towards students with special needs and inclusive education as expected. Kata Kunci : Special needs students, inclusion, attitudes, inclusion teachers, secondary students